Reporting of Service Efforts and Accomplishments. (Book Review). - Meyer, Philip E.; Hay, Leon E. (The Accounting Review, 1981)
Abstract Reviews the book "Reporting of Service Efforts and Accomplishments," by Paul K. Brace, Robert Elkin, Daniel D. Robinson, and Harold I. Steinberg.